SUPERVISI PENDIDIKAN AGAMA ISLAM (Kajian Al-QurÃ¢â¬â¢an dan Hadits) - Prabowo, Yoga Sari (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Empirically that strategic planning can be usefulhelp to assert focus on things that are reallyimportant, given the ease of the organization indetermining priority activities, optimizing theefficiency of the organization, provide support forthe establishment of smooth communication inexplaining the purposes of the strategy, help ingarnering support from internal and externalstakeholders, helping terkristalisasinya a betterunderstanding of the impact that may arise againstits decisions in the future and improvecoordination among the various activities andvarious units. As an educational institution, man 3Yogyakarta has a vision that will drive the future ofthe madrassa. The concept of vision is somethingthat is very important in management education.The vision of man 3 Yogyakarta is superior andskilled and mature personality that is shortenedwith an ultra prime.